PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH KOTA MAKASSAR - Asbi Amin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
This research aims to empirically examine the effect of regional financial statement presentation and accessibility of financial statements for accountability in financial management. The research was conducted in Makassar district, for two months. The sampling method used is proportionate stratified random sampling; the sample is then determined by 32 managers district and 32 financial staff of SKPD. Research applies for quantitative approaches. For this research the data analyzed using multiple linear regression with tools statistical program, after test the classical assumptions are met. The results of this research show that the presentation of the financial statements and the accessibility of the area of financial reporting partial or jointly positive effect on accountability in financial management.